Unemployment duration and disability: evidence from Portugal - Dario Sciulli; António Gomes de Menezes; José António Cabral Vieira (Institute for the Study of Labor (IZA), 2007)
In this paper we use Portuguese data on individual (multiple) unemployment spells and apply semi-parametric duration models to investigate the effects of different types of disabilities on (re)employment probabilities. We find that disabled persons with muscular, skeletal, geriatric and sensorial problems experience the longest unemployment spells. Organic (blind, deaf or linguistic) disabilities also significantly reduce the probability of finding a job, while intellectual or psychological disabilities do not. We also find that having previous employment experience and vocational training raise the probability of leaving unemployment into employment. Negative duration dependence and unobserved heterogeneity are also found in the data. Policies that seek to promote job accessibility should take into account the heterogeneous nature of the effects of different disabilities on reemployment.
Keywords: 330; Unemployment duration; disability; hazard models; Behinderte; Arbeitslosigkeit; Dauer; Berufliche Integration; Portugal